The Politics of Information / Problems of Policy in Modern Media - Smith Anthony (The Macmillan Press, 1978)
A series of recent articles all of which are designed to point up the political implications of decisions made in the communications field. Acknowledgements, Introduction, Broadcasting, Television as a Machine of Social Regulation, The Finance of Television, Social Accountability and Television, Management and Creativity in Television, Television Coverage of Northern Ireland, Community Conflict and the Media, The Press, State Intervention and the Management of the Press, Technology and Distribution and Editorial Control: Their Interactions in the Evolution of Journalism, A Telecommunications Future, Needs and Wants and Demands and Luxuries and Scarce Natural Resources, Notes and Reference, Index.